Analysis of Patient Satisfaction Levels Toward the Implementation of Electronic Prescribing (E-Prescribing) in the Outpatient Department of Jekulo Kudus Community Health Center - Ira Setia Lestari; Endang Setyowati; Intan Adevia Rosnarita (Advances in Healthcare Research, 2026)
Purpose: This study aimed to analyze patient satisfaction with the implementation of electronic prescribing (e-prescribing) in the outpatient department of Jekulo Kudus Community Health Center and to identify the relationship between patient satisfaction and respondent characteristics as well as service-related indicators. It was hypothesized that e-prescribing implementation was associated with a good level of patient satisfaction, although several service attributes still required improvement. Research Method: This study used an analytical observational method with a cross-sectional design involving 96 outpatients. Data were collected using a questionnaire based on five SERVQUAL dimensions: tangibles, reliability, responsiveness, assurance, and empathy. Data analysis included validity and reliability testing, univariate analysis, bivariate analysis using the Mann-Whitney test, and Importance Performance Analysis (IPA). Results and Discussion: Patient satisfaction was significantly associated with age, education level, health insurance status, and frequency of visits to the pharmacy clinic (p < 0.001), while gender, employment status, and number of medications received were not significantly related (p > 0.05). All SERVQUAL dimensions showed high perceived performance scores, indicating generally good satisfaction. However, IPA identified several priority areas for improvement, particularly the clarity of drug information, staff responsiveness, and patient attention. Implications: The findings indicate that e-prescribing has improved outpatient pharmaceutical services, but continuous efforts are needed to strengthen communication and patient-centered interaction. Further studies should explore system efficiency and long-term patient outcomes.